ХАРАКТЕРИСТИКА РОГІВ ЛОСЯ (ALCES ALCES) З УКРАЇНИ. - Волох, Анатолій Михайлович; Volokh, Anatolii (My University, 2019)
ENG During research of moose antlers from Ukraine, the following measurements were taken: coverage of the socket, circumference at a distance of 4 cm from the outer edge of the socket, length of each antler on the posterior curved side between the ends of the most remote upper and lower sprouts, number of sprouts at each corner, length of each spindle on the back side from the base to the end, circumference of each process in the middle, distance between the anterior proc- esses, maximum distance between the longest branches in the middle part, distance between the rear branches, width of the antler blade at the widest point. Given that in any population antlers of European adult moose are typical, intermediate, and deer-like, their measurements were taken respectively. The first postnatal antlers of moose from Ukraine reach 29.0 ± 2.55 cm in length, having in its composition 1–2 processes with a maximum width of 52.0–72.4 cm. The second antlers have 2–4 processes. The length of most of them (56.7 %) varies within 10–20 cm. Three-year-old animals, in comparison with the two-year-old ones, increase by 2 times the average length of the antler, by 1.8 times the width of the sockets and by 1.5 times the maximum antler width (71–117.3 cm). The dimensional characteristics of antlers in young moose are characterized by a considerable dynamics. The highest variation concerns the length of the processes, their number and circumference in the middle part, as well as the coverage of the sockets. The length of adult antlers is 40.1–98.0 cm, the width of the shovel is 6.0–24.2 cm, the girth of the trunk is 12.3–20.3 cm, and the maximum width is 72.3–146.2 cm. For a mass of 6.92–11.14 kg they have a low trophy quality: 191.30–303.51 points, which is the result of the absence of population management. A comparison of moose antlers from Ukraine with those from the south Russian macro population showed that the latter prevail by most of the parameters. For instance, antlers from Ukraine are 1.1 times smaller by circumference, blade width and total width and 1.5 smaller by length. The trophy qual- ity of antlers from the southern regions of Russia is significantly higher (268.4 points) than that in moose from Ukraine (234.4 points). ///// UKR Попри складну еволюційну долю та вилучення в Україні значної кількості європейського лося (офіційно з 1980 до 2016 рр. — понад 16 тис. особин: 2-ТП «Мисливство»), характеристика рогів цього величезного за розмірами ссавця є доволі слабко вивченим питанням. Навіть наші сусіди — білоруси (Козло, 1983) та росіяни (Тимофеева, 1974; Херувимов, 1969; Филонов, 1983; Данилкин, 1999; Данилов, 2005; Рожков и др., 2001, 2009 — список можна продовжувати), які мали у своєму розпорядженні значну кількість фактичного матеріалу, не приділяли дослідженню рогів лося особливої уваги. Лише у деяких з монографій висвітлено динаміку кількості відростків на них та обхвату їх розетки з віком (Язан, 1972; Филонов, 1973). Найбільш інформативними виявились результати дослідження лосів ( n > 500) із Московської і Тамбовської областей (Херувимов, 1969), у якому можна знайти дані про довжину, розвал рогів та небагато інших даних. Відомості з даного питання відсутні (Євтушевський, 2012) або дуже слабко розкриті і в інших українських виданнях (Волох, 2016). Між іншим, враховуючи велику цінність лося, як об’єкта трофейного полювання світово- го значення, до моніторингу його рогів пред’являють особливі вимоги (Фандеев, Никольская, 1983; Дема, Черепенин, 2005), які не відомі більшості наших зоологів. Тому ми поставили за мету дослідити роги лося із України, використовуючи сучасні методи.
Features of moose antlers (Alces alces) from Ukraine.
Keywords: moose; antlers; measurement; assessment; trophy; Ukraine; conservation; moose; antlers; measurement; trophy; assessment; conservation; Ukraine